Ropewalking and safety nets : local ways of managing insecurities in Indonesia - Koning, Juliette; H?usken, Frans (Social sciences in Asia ;, 2006)
This volume discusses how national and local social security in Indonesia has changed over the past decades and in particular during the economic and political crisis of the late 20th and early 21st century. The contributions, based on case studies from urban and rural Java, focus on the evolution of existing formal and informal institutions providing social security and at the ways in which people create access to such institutions and develop strategies to handle insecurities. The main conclusion is that informal institutions providing support to those who need it, more and more tend to exclude the poor and weak sections of society, and that government policy in this field is only beginning to address these major social issues.